Reflective practice and foreign language classroom anxiety: video-stimulated recall at work. Issue 6 (1st November 2016) - Cinkara, Emrah
Abstract: Reflective practices have been shown to improve the effectiveness of learning and teaching processes. In this study, video-stimulated recall technique was employed as a method of motivating language learners to reflect on their oral production tasks. In this experimental study, the Foreign Language Classroom Anxiety Scale (FLCAS) was administered to control and treatment groups before and after an eight-week module during which video-stimulated recall interviews were conducted with students in the treatment group. Statistical analyses revealed that pre- and post-test FLCAS scores differed within the treatment group but not within the control group. The results also suggested that stimulated recall is an effective reflective tool which assists students in noticing and reflecting upon the symptoms and causes of anxiety in the classroom.